MASSA OTOT BERKORELASI POSITIF DENGAN TOTAL AIR TUBUH PADA LANSIA: STUDI OBSERVASIONAL - Handayani, Maria Dara Novi; Adrianto, Nicholas; Dewi, Rita; Pakpahan, Hotmaria Agustina; Siswanto, Ferbian Milas (Media Penelitian dan Pengembangan Kesehatan, 2024)
Dehydration, the decrease of body fluid and electrolytes, is the most common disorder in the elderly. Total body water (TBW) is influenced by various factors including body composition, such as fat mass (FM) and fat-free mass (FFM). FM can be represented by body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) while FFM can be represented by muscle mass (MM). This study aimed to determine the correlation of BMI, WC, WHR and MM with TBW in the elderly. This cross-sectional research was conducted on elderly people in four nursing homes in Jakarta between November and December 2020. The sample was 87 people who meet the inclusion and exclusion criteria with the total sampling method. Fat mass data collection were carried out by trained personnel by measuring BMI, WC, WHR. MM data were collected using the Maltron Bioscan 916. Correlation analysis was carried out using the independent t-test and linear regression test. The results showed that the average TBW was 28.5 ± 5.4 liters (men were significantly higher than women). Further analysis showed that BMI, WC, and MM were positively correlated with TBW, but not WHR. In linear regression analysis, MM had the greatest correlation with TBW (p<0.05). This study validated that elderly people with lower muscle mass tend to have lower total body fluids; therefore, elderly people are advised to maintain muscle mass through diet and exercise modification to maintain total body fluids and reduce the risk of dehydration.